Comparative legal analysis of the regulation of the legal status of minors - Musabaev М.К.; Sabitov К.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
This study is devoted to the legal status of minors. The social disadvantage of Kazakhstani children, the existing problems in the implementation of the emerging juvenile policy of the state, the declarative nature of legislation, and the weak level of the legal protection of minors cause a public outcry and require the development of an effective response of the state. The above makes it possible to emphasize the necessity, importance, and timeliness of research in practice and law enforcement activities, problems of the legal status of minors, elements of its structure, and conceptual and categorical apparatus. The analysis of the legal literature related to the problems of the legal status of the individual has shown a variety of scientific approaches, theoretical constructions, and a significant terminological presence. The conducted research allows us to state that the content of the legal status of a minor is controversial. Researchers have not yet come to an unambiguous understanding of this issue, so they form it from various elements. Both from a scientific and legislative point of view, it is fair to note that the inclusion of new elements in the legal status enriches it not quantitatively, but qualitatively. It is concluded that the legal status of a child as a dynamic characteristic of his position in the state, experiencing the transformation of public life and state-legal phenomena, is undergoing modernization, reflecting the reform processes.